TINJAUAN YURIDIS PEMANFAATAN TANAH SETELAH DITETAPKAN SEBAGAI TANAH TERLANTAR PADA PUTUSAN PERKARA NOMOR 62/G/2013/PTUN.SBY - Vylla Nopvytasari; Sholahuddin Fathurrahman (MIZAN, Jurnal Ilmu Hukum, 2023)
The judge's reasons in resolving case number 62/G/2013/PTUN.SBY and the use of land that has been categorized as abandoned land are examined in this study. The goal of this research is to look into the legal aims theory that was used in this case's conclusion. The normative legal research method is used in this study. According to the findings of this study, the panel of judges in the trial reviewed the plaintiff's claim about Defendant I's determination of abandoned land because there are values that must be preserved by law and there is a causal relationship. One of the unfulfilled processes in the determination of abandoned land (1) The panel of judges believes that the official report on the identification and research of Defendant II's abandoned land is still incomplete and has not yet resulted in any legal consequences. (2) The panel of judges believes that the grounds for Defendant III's issuing of the State Administrative Decree is primarily based on Defendant I's State Administrative Decree. (3) The panel of judges requests that Defendants I and III have the State Administrative Decree issued revoked. (4) It is required to utilize abandoned land after it has been designated as such, although it has not been done so to date. (5)